Exploring The Strategies For Peace Action In Barangays With High Risk For Theft And Drug Cases - Samrudin L Masla; Ammar Y. Balimbingan; Michelle Van Claire Flores; Rosebelt S. Lomocso; Genesis Naparan (Journal of Governance and Administrative Reform, 2026)
Abstract This study examined the experiences of policy implementers in regulating taxicle operations in Pagadian City, with particular attention to their understanding of regulatory policies, the challenges they encounter in enforcement, the strategies they employ, and their recommendations for improving regulation. The study was conducted in response to continuing challenges in taxicle regulation, particularly issues related to driver compliance, colorum operations, and enforcement limitations. Using a qualitative case study design, data were collected through semi-structured in-depth interviews with seven (7) purposively selected participants. The data were analyzed using categorical aggregation to identify recurring patterns and categories. The findings revealed that policy implementers’ understanding of regulation is primarily developed through direct enforcement experience and reinforced through regular meetings, seminars, and continuous organizational communication. However, enforcement is constrained by driver resistance, largely associated with livelihood concerns, and by the presence of colorum drivers, which weakens regulatory efforts and affects compliance. In response, implementers use non-confrontational approaches that prioritize explanation and communication before penalties are imposed. Tricycles Operators and Drivers Association (TODA) organizations also support regulation through internal monitoring, policy reminders, and coordination with implementing agencies. The study concludes that taxicle regulation in Pagadian City reflects the principles of Michael Lipsky’s Street-Level Bureaucracy Theory, as implementation is shaped by practical experience, resource constraints, and discretionary decision-making. The study recommends strengthening driver education through improved seminars, enhancing coordination among implementing agencies, intensifying monitoring of illegal operations, and providing additional institutional support to improve the effectiveness and sustainability of taxicle regulation in Pagadian City. Keywords: policy implementers; Tricycles Operators and Drivers Association; Road Traffic Management Office; traffic enforcer; taxicle